Building Loyalty through Usability and Satisfaction with RedDoorz Website Services - Rinaldi Bursan; Nik Adzrieman Bin Abdul Rahman (IAIN Palopo, 2023)
This study aims to analyze the effect of satisfaction in building loyalty and positive word of mouth on RedDoorz users in Bandar Lampung. The main objective was to examine the effect of loyalty mediation on the effect of Word of Mouth satisfaction. To answer this goal, a quantitative research design was used by distributing questionnaires to 250 RedDoorz users. 200 usable data were analyzed with Structural Equation Modeling Analysis, Based on Covariance. The results showed that loyalty plays a role in mediating the effect of Word of Mouth satisfaction. That is, the higher the satisfaction of users or customers, the more loyalty is created, the more positive word of mouth will grow. This implies that the management must increase consumer loyalty in terms of financial transactions every time they make hotel reservations online because there are still complaints about financial transaction failures.